MSCs-derived HGF alleviates senescence by inhibiting unopposed mitochondrial fusion-based elongation in post-acute kidney injury - Kaiting Zhuang; Wenjuan Wang; Xumin Zheng; Xinru Guo; Cheng Xu; Xuejing Ren; Wanjun Shen; Qiuxia Han; Zhe Feng; Xiangmei Chen; Guangyan Cai (Stem Cell Research & Therapy)
Abstract Background The underlying mechanism of human umbilical-derived mesenchymal stem cells (hUC-MSCs) therapy for renal senescence in post-acute kidney injury (post-AKI) remains unclear. Unopposed mitochondrial fusion-based mitochondrial elongation is required for cellular senescence. This study attempted to dissect the role of hUC-MSCs therapy in modulating mitochondrial elongation-related senescence by hUC-MSCs therapy in post-AKI. Methods Initially, a unilateral renal ischemia–reperfusion (uIRI) model was established in C57 mice. Subsequently, lentivirus-transfected hUC-MSCs were given by subcapsular injection. Two weeks after transplantation, histochemical staining, and transmission electron microscopy were used to assess the efficacy of hUC-MSCs in treating renal senescence, fibrosis, and mitochondrial function. To further investigate the mitochondrial regulation of hUC-MSCs secretion, hypoxic HK-2 cells were built. Finally, antibodies of HGF and its receptor were used within the hUC-MSCs supernatant. Results Unopposed mitochondrial fusion, renal senescence, and renal interstitial fibrosis were successively identified after uIRI in mice. Then, the efficacy of hUC-MSCs after uIRI was confirmed. Subsequently, inhibiting hUC-MSCs-derived HGF significantly compromises the efficacy of hUC-MSCs and leads to ineffectively curbing mitochondrial elongation, accompanying insufficient control of elevated PKA and inhibitory phosphorylation of drp1 (Drp1pSer637). As a result, the treatment efficacy of renal senescence and fibrosis alleviation was also weakened. Furthermore, similar results were obtained with antibodies blocking HGF or cMet in hypoxic HK-2 cells treated with hUC-MSCs-condition medium for further proving. Uncurbed mitochondrial elongation induced by PKA and Drp1pSer637 was inhibited by hUC-MSCs derived HGF but reversed in the activation or overexpression of PKA. Conclusions The research concluded that hUC-MSCs-derived HGF can inhibit PKA-Drp1pSer637-mitochondrial elongation via its receptor cMet to alleviate renal senescence and fibrosis in post-AKI.